AEROSOL BEHAVIOUR OVER RANCHI - Lipi, Kumari; kumar, Manoj (European Scientific Journal, ESJ, 2013)
Atmospheric aerosols are important component in the radiation budget and generally tend to decrease the amount of solar radiation falling on earth. Some aerosols like BC are absorbing in the nature and affect the climate by increasing AOD and warming the climate. Its direct and indirect effect on environment and human health is partially known but more studies are needed to understand it properly. That is why it is important to do its Quantitative and qualitative analysis and study its impact on climate etc. Ranchi is comes under northern region which is most polluted region among India where many pollutants including BC are high in concentration, So this study of BC over Ranchi can help to know its concentration of BC is found to vary on a diurnal as well as seasonal basis. The role of atmospheric boundary layer is very important in the variation of BC concentration. The present study aims to find the relation of BC with the boundary layer and understand its variation. Further its impact on AOD and global radiation will also study. This research may form a small step towards a comprehensive study of black carbon aerosol in the atmosphere in the northern city Ranchi of India.